2020
DOI: 10.3389/fphar.2020.00555
|View full text |Cite
|
Sign up to set email alerts
|

Possible Genetic Determinants of Response to Phenytoin in a Group of Colombian Patients With Epilepsy

Abstract: Background: Epilepsy is a serious health problem worldwide. Despite the introduction of new antiepileptic drugs (AEDs) almost 30% of these patients have drug-resistant forms of the disease (DRE), with a significant increase in morbi-mortality. Objective: Our objective was to assess the impact of some genetic factors and its possible association with treatment response and adverse drug reactions (ADRs) to phenytoin in 67 adult Colombian patients with epilepsy. Methods: We conducted an analytical, observational,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…On the other hand, the association of the occurrence of ADR with genetic variants of cytochromes involved in drug metabolism appears as novel in regard of the treatment with PDE5i. This is particularly the case of rs1799853, a missense variant of CYP2C9 gene, predicted to be pathogenic by PolyPhen-2, and previously associated with a reduced drug metabolic function of the CYP2C9 cytochrome ( Helin et al, 2019 ; Calderon-Ospina et al, 2020 ). Although the potential pharmacokinetic impact of the identified genetic variants on the phenotype goes beyond the aim of this study, this evidence suggests that the occurrence of ADR may rely on individual fluctuations of the PDE5i serum levels due to functional variations of the enzymes involved in drugs metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the association of the occurrence of ADR with genetic variants of cytochromes involved in drug metabolism appears as novel in regard of the treatment with PDE5i. This is particularly the case of rs1799853, a missense variant of CYP2C9 gene, predicted to be pathogenic by PolyPhen-2, and previously associated with a reduced drug metabolic function of the CYP2C9 cytochrome ( Helin et al, 2019 ; Calderon-Ospina et al, 2020 ). Although the potential pharmacokinetic impact of the identified genetic variants on the phenotype goes beyond the aim of this study, this evidence suggests that the occurrence of ADR may rely on individual fluctuations of the PDE5i serum levels due to functional variations of the enzymes involved in drugs metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The rs1799853 polymorphism in the CYP2C9 gene has been linked to the incidence of T allele, which four times increases the likelihood of medication resistance in individuals with epilepsy [ 28 ]. The FDA (Food and drug Administration authority) has updated the clinical pharmacology part of the phenytoin label to include a warning concerning the risk of abnormally high levels in individuals who have specific CYP2C9 allelic variations [ 29 ]. Another study found a link between CYP2C9 polymorphisms and lower phenytoin metabolism and improved medication responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CYP2C9 gene is highly polymorphic and as of to date more than 60 variant alleles, some of which are associated with reduced function or even non-functional protein have been described (PharmGKB, 2020). Reduced clearance of the CYP2C9 substrates such as (S)-warfarin and phenytoin among carriers of defective alleles could results in significant bleeding complications or neurotoxicity respectively (Kidd et al, 2001;Jorgensen et al, 2012;Kawai et al, 2014;Calderon-Ospina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%